21st Century Librarians At The Crossroads: Specialized Competencies Needed - Ismail, Saidatul Akmar; Shahibi, Mohd. Sazili (2015)
Library work traditionally involves a process of collecting, promoting and circulating data and information. The work processes should be a means to an end. With the advancement of the Internet and online technologies, the traditional prosess of library work and the advancement of the technologies have to be integrated and require a certain type of thinking skills which involve the left-and right-brain activities. This paper attempts to highlight the processes of thinking that seem necessary for the libraries of today to manage technology effectively. The librarians must also be able acquire new competencies and discover opportunities for improving services through tapping along with these technologies. Curriculum pertaining to the development of the 21st century librarians and information professionals is also discussed in order to ensure that the new breed of information professionals are able to act as change agents in society.